Study of intestinal function in anorectal malformations: the role of Bowel management in quality of life - Lombardi, Laura; Garrisi, Elena; Ricco', Matteo; Marchesi, Federico; Casolari, Emilio; Gatti, Claudia; Del Rossi, Carmine G (Acta Biomedica Atenei Parmensis, 2016)
Purpose: We aimed at investigating bowel function in children and adolescents with anorectal malformations (ARMs) and assess their quality of life (QoL), in order to define a personal program of bowel management improving both clinical condition and self-confidence. Methods: A total of 55 patients treated for ARM by Posterior Sagittal Ano-Recto-Plasty (PSARP) from 2000 to 2014 were included into the study. The parents of 41 patients answered two telephone questionnaires about the parents’ self-efficacy and about QoL (GIQLI). A modified Peña score system was used to evaluate intestinal function. Twenty patients underwent anorectal manometry. After clinical assessment, all patients underwent an individual bowel management program. A median follow-up of 91.3 months was performed. Results: A significant inverse correlation was found between Peña score and GIQLI (r:-0.93, p